Miracles from Heaven - Riggen, Patricia; Roth, Joe, 1948-; Jakes, T. D.; Franklin, DeVon; Brown, Randy (Screenwriter); Garner, Jennifer, 1972-; Rogers, Kylie, 2004-; Henderson, Martin, 1974-; Lynch, John Carroll, 1963-; Derbez, Eugenio; Queen Latifah, 1970-; Siliotto, Carlo, 1950-; et al. (Culver City, California Sony Pictures Home Entertainment, 2016)
Based on the incredible true story of the Beam family. When Christy discovers her ten-year-old daughter Anna has a rare, incurable disease, she becomes a ferocious advocate for her daughter's healing as she searches for a solution. After Anna has a freak accident and falls three stories, a miracle unfolds in the wake of her dramatic rescue that leaves medical specialists mystified, her family restored and their community inspired.
"The sweet sincerity of Miracles From Heaven makes it hard to dislike."--New York Post
"Riggen effectively creates a sense of how intimidating hospitals and medical procedures are for a child, often shooting from Anna's perspective. The emphasis on Anna and Christy's experience of these trials is a smart choice."--Los Angeles Times
"The harrowing medical crisis that drives the family story gives it the nonreligious urgency to preach beyond the choir. So too does Jennifer Garner's down-to-earth lead performance."--Hollywood Reporter
Originally released as a motion picture in 2016.
Based on the book by Christy Beam.
Widescreen (1.85:1).
Special features: commentary with Patricia Riggen and Randy Brown; Miracles abound: the making of Miracles from Heaven; Bearing witness; Your words music montage; Creating Heaven.
Music, Carlo Siliotto ; editor, Emma E. Hickox ; director of photography, Checco Varese.
Jennifer Garner, Kylie Rogers, Martin Henderson, John Carroll Lynch, Eugenio Derbez, Queen Latifah.
Keywords: Beam, Annabel, -- 2002- -- Drama; Beam, Christy Wilson -- Drama; Rare diseases -- Drama; Near-death experiences -- Drama; Miracles -- Drama; Mothers and daughters -- Drama; Families -- Drama; DVDs; Drama films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Film adaptations; Christian films; Biographical films; Feature films; Fiction films